The Influence Of Crisis Leadership, Knowledge Management And Innovation Culture On Organizational Resilience In Higher Education Institutions - Ardiyanto Maksimilianus Gai; Chairul Anwar; Samuel PD Anantadjaya; Iwan Henri Kusnadi; Tyahya Whisnu Hendratni; Dasep Supriatna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Higher education institutions need to establish strong organizational resilience because their educational systems must adapt to sudden unpredictable changes that occur in their dynamic environments. The research investigates the relationship between crisis leadership knowledge management and innovative work environments and their impact on institutional resilience at higher education institutions. The researchers conducted their study through a quantitative research method which used an explanatory research design. The study collected data through a structured questionnaire which surveyed 180 participants who worked as unit leaders and lecturers and educational staff members from different Indonesian higher education institutions that the researchers selected through purposive sampling method. The researchers used multiple linear regression to analyze data after they finished testing validity and reliability and classical assumptions. The study demonstrates that organizations achieve resilience through the combination of crisis leadership activities and knowledge management practices and innovation work environment implementation. The research demonstrates that leadership attributes and cognitive elements and cultural components work together to establish organizational resilience in higher education institutions. The research findings show that sustainable organizational resilience practices enable higher education leaders to create policies which enhance institutional adaptability.